Patterns of Reduplication in Tajionese: The Case of Celebes Malayo-Polynesian Language - Suparni, Suparni; Putra, Rizky Anugrah; Aziz, Muhammad Fahruddin (SCOPE: Journal of English Language Teaching, 2024)
The current study was employed to investigate how the form and meaning of reduplication are contained in the Tajionese. Furthermore, the study also aimed to describe the morphosemantic attributes of Tajionese reduplication. The researcher obtained the data from the Tajionese natives. The data collected in this study used in-depth interviews with the local tribesman and also the tribe's elder. The data is analyzed using distributional techniques and padan techniques. The study successfully revealed that Tajionese reduplication has 3 primary forms: full reduplication, partial reduplication, and reduplication in combination with affixes. Unexpectedly, those reduplications tend to form specific word categories such as nouns, verbs, adjectives and adverbs. The researcher revealed that the reduplication in Tajionese contains several meanings, namely (1). states plural meaning (2) states the meaning that is done repeatedly (3) states the resemblances (4) states the meaning somewhat (5) states the meaning is very (6) states the meaning of the act done comfortably with ease or with pleasure.